Aquired causes of ureteral stenosis : A study at tishreen university hospital (2021-2022) - كرو, مؤمن; محمد كنعان; ايمن حرفوش (Latakia University Journal -Medical Sciences Series, 2023)
* The importance and justification of the research: After the increase in the popularity of endoscopic urological procedures for diagnostic or therapeutic reasons, the percentage of unnecessary procedures, whether for diagnosis or selecting a specific treatment method from among multiple options, increased with it. Which led to an increase in the rate of complications, including ureteral strictures, which we may be indispensable. . This study aims to explore these strictures and their prevalence statistically in order to clarify their importance and the need to use laparoscopic procedures when needed only. * The Aim: A study of the prevalence of acquired ureteral strictures among patients of Tishreen University Hospital. * Patients and methods: Study type: prospective observational study. The study sample consisted of (55) patients who reviewed the Urology Department at Tishreen University Hospital / Lattakia / and were diagnosed with ureteral stenosis between the years 2021-2022. The sample was divided according to the cause of ureteral stenosis into: 1- Benign acquired ureteral strictures: -of medical (Iatrogenic) origin. - of non-medical origin. 2- Acquired, malignant strictures of the ureter: -external in origin, pressing on the ureter. -Endogenous at the expense of the ureteral lumen. Distribution of the sample size according to the sex of the patient (male or female) Distribution of the sample size according to the age of the patient, and the sample was divided into three age groups (30, <30 – 60, >60). Sample size distribution according to the direction of stenosis (unilateral or bilateral) Distribution of the sample size according to the site of the stricture (upper, middle or lower). * Results: The total sample size was 55 patients with a mean age of 48 years. The study concluded that the most common causes are: benign acquired strictures of medical (Iatrogenic) origin, which amounted to 60% of the total sample size, benign acquired strictures of non-medical origin, which amounted to 30.9% of the total sample size, and malignant acquired strictures of external origin resulting from For external compression of the total sample size 7.3%, acquired malignant strictures of internal origin at the expense of the ureteral lumen of the total sample size 1.8%. When studying the relationship between the age of the patient and the cause of the Strectures, it was found that there was a statistically significant difference for the control of the age group (30-60) years due to the occurrence of ureteral stenosis due to a medical reason . This is explained by the prevalence of invasive medical interventions in this age group, and they also have a tendency for the occurrence of stenosis due to non-medical reasons. As for the age group < 60 years, it was the most common cause of malignant external origin, and this is explained by the large external tumors that were discovered by chance in this age group. When studying the relationship between the side of the stenosis and the cause of the stenosis, it was observed that unilateral stenosis dominated over benign acquired causes of medical origin. Benign acquired causes of non-medical origin, and this is explained by the prevalence of bilateral injury in the context of retroperitoneal fibrosis and after radiotherapy treatments, as well as if unilateral stenosis dominated over malignant acquired causes, and this explains the prevalence of unilateral tumors more than bilateral tumors. By studying the location of the stricture according to each causal group, we noticed: The dominance of the lower site for the occurrence of benign acquired strictures of medical origin, and this is due to the natural angulation of the ureter in this region and the difficulty of medical maneuvers, which makes it more vulnerable to trauma during endoscopy, as well as the proximity of the ureter to the female pelvic organs, which exposes it to infection. During surgical interventions on the pelvis. We also noticed that the lower site dominated the occurrence of stenosis due to malignant exogenous origin, and this explains the reason for the prevalence of tumors in the organs adjacent to this site compared to other sites.. *Conclusion: The most common cause of ureteral strictures are benign acquired strictures of medical (Iatrogenic) origin. The most common site of ureteral stenosis is the inferior site. Unilateral ureteral stenosis is the most common.